2021
DOI: 10.14202/vetworld.2021.2397-2409
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional properties of gelatin from goat bone through alcalase and neutrase enzymatic extraction

Abstract: Background and Aim: Gelatin is a dissolved protein that results from partial extraction of collagen, commonly from pig and bovine skin. There was no study on gelatin production from Kacang goat bones through enzymatic extraction. This study aimed to evaluate the chemical, physical, and functional properties of gelatin from bones of Kacang goat using alcalase and neutrase enzymes. Materials and Methods: Male Kacang goat bones aged 6-12 months and two commercial enzymes (alcalase and neutrase) were used for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…From the previous literature, it was shown that as compared to cow bone, higher concentration of TC, TN and other macro/micronutrients were recorded in the goat bone (Samoraj et ). It was also found that higher quantity of gelatin could be recorded in the bones of goat (Matulessy et al 2021). Therefore in the present study, the biofertilizer made from goat bone showed more plant growth as compared to that of biofertilizer made from cow.…”
Section: Discussionsupporting
confidence: 60%
“…From the previous literature, it was shown that as compared to cow bone, higher concentration of TC, TN and other macro/micronutrients were recorded in the goat bone (Samoraj et ). It was also found that higher quantity of gelatin could be recorded in the bones of goat (Matulessy et al 2021). Therefore in the present study, the biofertilizer made from goat bone showed more plant growth as compared to that of biofertilizer made from cow.…”
Section: Discussionsupporting
confidence: 60%
“…As shown in Figure , HNBC was rich in glycine (Gly, 253 residues), alanine (Ala, 124 residues), and proline (Pro, 99 residues), which was similar to amino acid compositions of many other bone collagens. ,,, Generally, Gly is the major amino acid and occurs as every third residue in collagen. The Gly content in HNBC was 253 residues/1000 residues, which was lower than those of many bone collagens (320–340 residues) but higher than that of channel catfish head bone gelatins (only more than 20%) and similar to Kacang goat bone gelatin . In addition, the content of glutamic acid (Glu) with 102 residues/1000 residues in HNBC was significantly higher than that in collagens from the carp bone (76 residues), black drum bone (68.7 residues), sheepshead bone (65.8 residues), deep-sea redfish bone, and leather jacket bone (35.8 residues) .…”
Section: Resultsmentioning
confidence: 87%
“…The Gly content in HNBC was 253 residues/1000 residues, which was lower than those of many bone collagens (320–340 residues) but higher than that of channel catfish head bone gelatins (only more than 20%) 42 and similar to Kacang goat bone gelatin. 43 In addition, the content of glutamic acid (Glu) with 102 residues/1000 residues in HNBC was significantly higher than that in collagens from the carp bone (76 residues), black drum bone (68.7 residues), 28 sheepshead bone (65.8 residues), 28 deep-sea redfish bone, 44 and leather jacket bone (35.8 residues). 29 Pro- and hydroxyproline (Hyp) were the unique amino acids in collagen, and their content is greatly related to the thermal stability of collagen.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin is a protein obtained by the hydrolytic degradation of collagen from porcine or bovine origin. 58,59 It contains 18 different types of amino acids among which glycine, hydroxyproline and proline are the chief constituents of the total amino acid content. 60 For food industry, collagen is either boiled or enzymatically hydrolyzed to obtain colorless gelatin.…”
Section: Electrospinning – Backgroundmentioning
confidence: 99%